Impacto de la comunicación organizacional en la calidad de servicios a los usuarios en el Hospital del IESS, cantón Quevedo, año 2021 - Seniterra Romero, Alexis Andrea (2021)
Organizational communication is the main axis in an institution to define the obligations and responsibilities that each of the members in an organization has, communication influences the information processes in the work environment. The organizational culture expresses through strategies facilitating commitment and reinforcing the unity of the organization, and in turn generates control and guides behaviors in organizations. Communication in user services allows to know the quality of service in the user service area, the environment in which employees work in each of the areas. Organizational communication becomes a fundamental factor in planning, organization and control functions, and this is where its importance lies. The survey technique has been applied, a questionnaire with closed questions is carried out, it is determined to formulate a proposal that allows the design of a communication plan to contribute to the improvement in the quality of care for users at Hospital General Quevedo IESS.